Oil spill emergency response in the Barents Sea : issues of interorganizational coordination. - Sydnes, Maria (Universitetet i Tromsø, 2012)
Papers 2, 3 and 4 of this thesis are not available in Munin: 2. Ivanova, M. and Sydnes, A.K.: 'Interorganizational coordination in oil spill emergency response: a case study of the Murmansk region of Northwest Russia', Geography (2010), 33 (3), pp. 139‒164. Available at http://dx.doi.org/10.1080/1088937X.2010.545755 3. Sydnes, M. and Sydnes, A.K.: 'Oil spill emergency response in Norway: coordinating interorganizational complexity', Polar Geography (2011), 34 (4), pp. 299-329. Available at http://dx.doi.org/10.1080/1088937X.2011.620721 4. Sydnes, M. and Sydnes, A.K.: 'The Norwegian‒Russian oil spill response regime in the Barents Sea: an untold story of success', In: E. Røsæg & A. Proelss, eds. Safety in the North. Studies in international law of the sea and maritime law series. Baden-Baden : Nomos (forthcomming manuscript) Following the substantial increase in maritime transport and offshore industrial developments in the Arctic areas, accidental discharge of oil from ships in the Barents Sea has become recognized as a significant threat in Norway and northwest Russia. This study examines how oil spill emergency response (OSER) is organized on the Norwegian and Russian sides of the Barents Sea and how cooperation between the two states has been established. In focus here is the problem of interorganizational coordination. The analysis is based on the premise that the effectiveness of an OSER system is a function of the ability of the actors to coordinate their activities. The study outlines the main actors and formal organizational structure of the Norwegian and Russian OSER system. It further examines patterns of interorganizational coordination and shows how such formal and informal mechanisms as various aspects of coordination interact to provide effective functioning of the system. It studies how interdependence is created among organizations in OSER systems and how this affects organizational behaviour in terms of interorganizational coordination. Finally, it discusses the key characteristics of the ...